A feasibility study on La Verde refined bottom ash and engineered structural fill - Abellera, Giancarlo M.; Baking, Lourdes Teresa P.; Banson, Gerardo Iñigo M.; Wee, Lance Charleson Y. (College of Engineering, University of the Philippines Diliman, 2012)
The objective of the study is to determine whether the La Verde Refined Bottom Ash and Engineered Structural Fill made from the processing of bottom ash, is a feasible undertaking. It should be a relatively cheaper alternative to the current structural fills available, while providing a solution to the ash disposal problem of coal-fired power plants in the country. This feasibility study is divided into four parts where the different factors and measures were considered to assess the feasibility of the product: Market Study, Technical Study, Financial Study, and Social Profitability Study. The first part, the Market Study, is where the demand for the product has been determined and how this need would be addressed through the product's capabilities. The potential customers and competitors of the La Verde RBA and ESF were identified. Marketing schemes and strategies were also designed and created to reach the identified markets of the product. After proving that there is indeed a market for the product, the group proceeded to the second part of the study which is the Technical Study. Suppliers for the different materials and equipment needed to produce the RBA and ESF were identified. This is where the specific requirements such as the processes, labor, equipment and materials needed, and facilities, for operating a business offering the RBA and ESF were evaluated. Putting into consideration the costs needed to run the business, the results show that La Verde is a profitable business. Also, initial startup costs amount to about Php 48 Million which covers the first three months of business operations. La Verde hopes to source its funding from 3 places: through owner's equity, medium term bank funding programs, and capital ventures/angel investors. Looking at the projected income statements and balance sheets for the first 5 years of operation, La Verde proves to be not only profitable, but of high potential growth with high values such as 0.99 net profit margin and 170% for the IRR of La Verde. Looking at the social profitability of La Verde, each benefit along with its corresponding costs was enumerated. Also, 9 stakeholders were determined. Each stakeholder's benefit was discussed. Both quantitative and qualitative benefits were taken note of. Lastly, it was proven through a benefit-cost ratio of 1.85 that the project is socially profitable. Overall, the La Verde project was found to be feasible.